Length-Weight Relationship, Condition Factor and Feeding Habit of Fishes from Mangrove of Santubong Estuary, Sarawak, Malaysia - Farah, Akmal Idrus; Fazimah, Aziz; Adriana, Christopher Lee (UNIMAS Publisher, 2021)
Length-weight relationship (LWR), condition factor (K) and feeding habits of Coilia dussumieri, Nemapteryx nengaand Nibea soldadofrom Santubong Estuary, Sarawak, Malaysia were reported in the present study. The sampling was conducted during the non-monsoon season and monsoon season from April to November 2017 at Buntal, Penambir and Demak rivers using three-layered gillnets. A total of 182 fish samples were caught and measured for the total length and body weight. Then, the data were analysed by the equations for LWR and K. The feeding behaviour analysis was carried out using Relative Gut Index (RGI) and Frequency of Food Occurrence method. The log-transformed regression showed that most of the fishes exhibited negative allometric. K showed a significant difference between seasons. The RGI values of the fishes showed that they were carnivorous. The highest frequency of food occurrence in both seasons was gastropods (94-95%) and the food items were found to be more variable during monsoon season (gastropodsinsect, worms, fish, asteroidea, phytoplankton and bivalve). The b value is an exponent to measure the growth pattern of fish and in this study, the b values were in the expected range of 2.5-3.5 and not affected by seasonal variation. The K values suggesting that most of the species were surviving well in the river and was influenced by seasonal change. The RGI and frequency of food occurrence showed that all fish in this study species were carnivorous with more variability in food was observed during themonsoon season. The data of this study are important for a sustainable fisheries management in this area.